2001
DOI: 10.1074/jbc.m105572200
|View full text |Cite
|
Sign up to set email alerts
|

Different Subtypes of α1-Adrenoceptor Modulate Different K+ Currents via Different Signaling Pathways in Canine Ventricular Myocytes

Abstract: Multiple subtypes (␣ 1A , ␣ 1B , and ␣ 1D ) of ␣ 1 -adrenoreceptors (␣ 1 ARs) co-exist in the heart and mediate a variety of cellular functions. We studied ␣ 1 AR modulation of inward rectifier (I K1 ) and transient outward (I to ) K ؉ currents in canine ventricular myocytes. Phenylephrine at 10 M depressed only I to without affecting I K1 and at 100 M inhibited both I to and I K1 . The effect of phenylephrine on I to was abolished by (؉)niguldipine (10 nM Over the past decade, evidence from pharmacological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Western immunoblot analysis confirmed an increase in active CaMKII (see also ref. 13) in parallel with the potentiation of I Ca,L . Also, we showed that PKC, which is activated by the Gq-phospholipase C-diacylglycerol pathway (2), is involved in the activation of CaMKII during ␣ 1 ARS, based on the similar effects of CaMKII and PKC inhibition on I Ca,L in the presence of phenylephrine.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Western immunoblot analysis confirmed an increase in active CaMKII (see also ref. 13) in parallel with the potentiation of I Ca,L . Also, we showed that PKC, which is activated by the Gq-phospholipase C-diacylglycerol pathway (2), is involved in the activation of CaMKII during ␣ 1 ARS, based on the similar effects of CaMKII and PKC inhibition on I Ca,L in the presence of phenylephrine.…”
Section: Discussionmentioning
confidence: 89%
“…KN-93 and KN-92 were obtained from Calbiochem, and 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid (BAPTA)-acetoxymethyl ester was obtained from Molecular Probes. Antiphospho-CaMKII (anti-active CaMKII, rabbit polyclonal IgG raised against threonine phosphorylated peptide corresponding to the phosphorylated Thr-256 region of the mammalian CaMKII) was obtained from Promega (12,13). Anti-total CaMKII (mouse monoclonal IgG raised against amino acids 303-478 of CaMKII of mouse origin) was obtained from Santa Cruz Biotechnology (12).…”
Section: Fig 4 Localization Of Activated Camkii In Response To ␣1armentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in the present study, neither PLC nor PKC inhibition caused a significant reduction in the effect of PE on rat I to . On the other hand, it has been demonstrated that ␣ 1 -adrenoceptor stimulation reduces the amplitude of the cardiac I to through PKC activation in the dog (45). This difference could be due to the different channels that underlie I to in the different species.…”
Section: Discussionmentioning
confidence: 98%
“…The use of these inhibitors, particularly GF109203X, in myocardial tissue and cells has implicated PKC-mediated signalling events in the regulation of physiological functions, such as contraction (Pi & Walker, 2000;Szokodi et al, 2002;von Lewinski et al, 2003) and protein synthesis (Ponicke et al, 1999), as well as a variety of pathophysiological processes, such as myocyte hypertrophy (Mullan et al, 1997;Ponicke et al, 1999;Ruf et al, 2002) and ischaemic cell death (Kitakaze et al, 1996;Chen et al, 1999;Inagaki et al, 2000;Fryer et al, 2001). In addition, GF109203X and Ro31-8220 have been used to investigate the roles of PKC in the regulation of sarcolemmal ion-transporting proteins, such as K þ (Hu et al, 1996;Wang et al, 2001a), Ca 2 þ (Woo & Lee, 1999;Hu et al, 2000) and Cl À (Middleton & Harvey, 1998;Duan et al, 1999) channels and the Na þ /K þ pump (Jo et al, 2000). These inhibitors have also been utilised by this and other laboratories to explore the involvement of PKC isoforms in the stimulation of the sarcolemmal Na þ /H þ exchanger (NHE1) by diverse stimuli, such as adrenergic (Puce´at et al, 1993;Snabaitis et al, 2000), thrombin (Yasutake et al, 1996), angiotensin (Gunasegaram et al, 1999) and opioid (Bian et al, 2000) receptor agonists, anaesthetic agents (Kanaya et al, 2001) and oxidative stress (Snabaitis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%